Protective effects of hypoxic conditioning treatment on brain and cardiac tissues following thoracic aorta occlusion - Jun Xu; Fang Tong; Yumeng Wang; Sijie Li; Wenbo Zhao; Xiaomei Tian; Fengyong Liu; Xunming Ji; Changhong Ren (Brain Circulation)
BACKGROUND: Thoracic aortic ischemia-reperfusion (I/R) injury occurs in clinical scenarios and can lead to damage in organs such as the spinal cord, kidneys, and intestines. Hypoxic postconditioning (HyP) has shown promise in reducing organ I/R injury, suggesting its potential applicability in thoracic aortic I/R injury. However, the pathological damage caused by thoracic aorta occlusion (TAO) to the heart and brain is not yet well understood. This study aims to investigate the protective effects of hypoxic conditioning (HyP) treatment on brain and cardiac tissues following TAO-induced I/R injury. MATERIALS AND METHODS: Male C57BL/6 mice were used to construct the TAO model by blocking the thoracic aorta for 0.5 or 1 h, followed by 24 h of reperfusion. The mice were divided into five groups: sham, TAO (0.5 h), TAO (0.5 h) +HyP, TAO (1 h), and TAO (1 h) +HyP. Hematoxylin and eosin, Masson, and Sirius red staining were performed to assess morphological changes and collagen deposition in brain and heart tissues. Protein expression assays were conducted to quantify inflammation-related proteins in the serum. RESULTS: The results showed that TAO caused significant neuronal damage in the hippocampal regions (CA1, CA3, and DG) and myocardial cell damage with collagen deposition. HyP treatment significantly alleviated these damages, particularly with shorter ischemic durations (0.5 h). Specifically, in cardiac tissues, HyP treatment reduced myocardial injury and collagen deposition. In addition, HyP treatment modulated systemic inflammatory responses, as evidenced by the increased expression of anti-inflammatory proteins such as interleukin 13 (IL-13) and the decreased expression of pro-inflammatory proteins such as IL-6, IL-12p70, IL-17, and tumor necrosis factor-α. CONCLUSION: HyP treatment significantly mitigates brain and cardiac tissue damage caused by TAO, especially with shorter ischemic durations. These findings highlight the potential clinical application of HyP treatment in reducing TAO-induced tissue damage and inflammation, offering a novel therapeutic option for patients with thoracic aortic I/R injury. Future studies should further investigate the mechanisms and optimal implementation protocols of HyP treatment to maximize its clinical value.